INKULTURASI LITURGI KATOLIK DALAM PEMBENTUKAN IDENTITAS BUDAYA DAN RELIGIUS MAHASISWA CALON KATEKIS SUKU BATAK - Tobing, Ona; Tibo, Paulinus; Muri, Herkulianus (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2024)
Local culture has extraordinary wealth for the people who have it and makes a value in life. One of them is Batak culture which is maintained to increase awareness of cultural identity and faith, increase participation in church activities from various cultural changes in society, especially students as a young generation. This has an impact on the inculturation of local culture (Batak culture) in the Church through Catholic Liturgy. This research aims to find out the main elements in inculturative liturgy, namely aspects of language, building architecture, liturgical music, liturgical clothing and dance movements are cultural artworks that have the values of Batak community life and become an attraction for Catholic students as a form of love for local wisdom. This research uses descriptive qualitative methods with interview techniques, data collection through documentation and direct observation related to the facts that occur about the implementation of liturgical inculturation. Key informants in this research include Catholic students, Parish pastoral council and parishioners and cultural leaders. The research findings show that Catholic students understand the basic concept of Catholic liturgical inculturation of local culture in the form of Church music, dance, clothing, singing, architectural forms of Church buildings and language. Another finding is that students' love for local culture (Batak culture) in the Catholic church liturgy is evidenced by taking part in the celebration of the inculturation liturgy. This research shows that Catholic students have an understanding and love for local culture in the celebration of the inculturation Eucharist.